2015
DOI: 10.4094/chnr.2015.21.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Preschoolers’ Smartphone Addiction Tendency, Their Problem Behaviors, and Parenting Efficacy of Their Mothers

Abstract: Purpose:The purpose of this study was to explore the relationships among preschoolers' smartphone addiction tendency, problem behaviors, and parenting efficacy of the mothers of these children. Methods: A cross-sectional, descriptive study design was used with self-administered questionnaires. A total of 83 mothers of preschoolers aged 4-6 years and their preschool teachers from a kindergarten participated in the study. Results: Mean daily time spent by the preschoolers on smartphones was about 45 minutes/day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The timing of device use (e.g., whether they were used around bedtime) was measured in one sample (Beyens & Nathanson, 2019;Nathanson & Beyens, 2018a, 2018b. Five studies measured parental perceptions of excessive or problematic use by young children, using various terminology including smartphone addiction proneness (Cho & Lee, 2017), addiction tendency (Lee et al, 2015), over-dependency (Lee & Park, 2018), and immersion tendency (Kim & Hwang, 2017). One study (Hutton et al, 2020) only reported whether a child had access to their own mobile device.…”
Section: Smartphone Tablet and Child-factor Measurementmentioning
confidence: 99%
“…The timing of device use (e.g., whether they were used around bedtime) was measured in one sample (Beyens & Nathanson, 2019;Nathanson & Beyens, 2018a, 2018b. Five studies measured parental perceptions of excessive or problematic use by young children, using various terminology including smartphone addiction proneness (Cho & Lee, 2017), addiction tendency (Lee et al, 2015), over-dependency (Lee & Park, 2018), and immersion tendency (Kim & Hwang, 2017). One study (Hutton et al, 2020) only reported whether a child had access to their own mobile device.…”
Section: Smartphone Tablet and Child-factor Measurementmentioning
confidence: 99%
“…Visual plays, i.e., playing games and watching video, on the phone are static, isolated plays. They prevent children from engaging with other children and isolate them from relationships (Lee et al, 2015). Such type of play does not stimulate children's imagination.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an increase in the duration of smartphone use increased the odds of being in the risk group by 3.15 times. Although there is a slight difference in the duration range of smartphone use, the risk of addiction was also significant in other studies [5,6,11]. In particular, using a smartphone for more than an average of 30 minutes per day significantly increased the risk of smartphone dependence or addiction, and the risk increased linearly with the duration of use [5,11].…”
Section: Discussionmentioning
confidence: 91%
“…Although there is a slight difference in the duration range of smartphone use, the risk of addiction was also significant in other studies [5,6,11]. In particular, using a smartphone for more than an average of 30 minutes per day significantly increased the risk of smartphone dependence or addiction, and the risk increased linearly with the duration of use [5,11]. These findings show that an excessive increase in the duration of smartphone use in preschool-age children's daily lives may be the most important variable for addiction risk.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation